IDENTIFIKASI KADAR GLUKOSA DAN SUKROSA PADA MADU HUTAN - ZUHAIRIAH NST; ERNALA BR GINTING; DYNA GRACE ROMATUA; FIRDAUS FAHDI (Jurnal Penelitian Farmasi & Herbal, 2019)
Abstract Glucose and sucrose tests are performed as one of honey’s standard quality. Meanwhile the process of honey production by bees itself is a complex process, so there is a high probability of differences in the levels and composition of glucose and sucrose among the types of honey circulating in the community. The composition of glucose and sucrose of each honey can affect its efficacy mainly when it is used for treatment process. The aim of this research is to know glucose and sucrose level in forest honey and compare it with honey’s standard quality according to Indonesian national standard (SNI 01-3545-2013). The samples were 3 forest honey from different village. Sample A is forest honey from Kubu Simbelang Village, Sample B from Bunuraya Village, and Sample C from Suka Village, Tigapanah District. The determination of glucose and sucrose levels was performed by Luff Schoorl method. The result of this study was glucose average level of each sample A, B and C is 71,42%, 66,24%, and 71,21%. The sucrose average levels of sample A, B, and C is 3,09%, 4,51, and 3,04%.It can be stated thatall forest honey used in this study has fulfilled the requirements according to SNI 01-3545-2013 which set that glucose level of honey must be at least 65%while the sucrose level is maximum 5%.